Diversity of mosses in Mt. Data National Park, Luzon Island, Philippines - Policarpio, Mary Gold C.; Tolentino, Maria Leonora C. (2014)
Thirty (30) species of moss, belonging to twenty (20) families were observed using gradsect, plotless, and quadrant sampling during the study in Mt. Data National Park, Luzon Island, Philippines. Two sites were sampled - mossy forest and pine forest. In this study, Mt. Data National Park has a high Simpson's Index of Diversity and Shannon-Wiener Index, having the values of 0.89 and 2.49 respectively. The study revealed seven new records of mosses in Mt. Data namely, Brachythecium buchnanii, Macromitritrium angustifolium, Trachypus humilis, Claopodium assurgens, Chionoloma angustata, Lopidium struthiopteris and Acroporium strepsiphyllum. Monitoring and conservation of Mt. Data National Park is recommended to prevent exploitations leading to its destruction -- Author's abstract.
Thesis (Bachelor of Science in Biology)--University of the Philippines, 2014.
Includes bibliographical references (leaves 31-33).
Keywords: Mosses -- Philippines -- Mt. Data National Park (Luzon).